ANALISIS TINGKAT KERENTANAN MASYARAKAT TERHADAP BANJIR ROB DI KECAMATAN TEGAL BARAT KOTA TEGAL TAHUN 2021 - Ramadhanty, Nisa Rizqi; Muryani, Chatarina; Tjahjono, Gentur Adi (INDONESIAN JOURNAL OF ENVIRONMENT AND DISASTER, 2022)
ABSTRACT The city of Tegal is one of the cities directly adjacent to the Java Sea. The problem of tidal inundation, especially in the District of West Tegal, is one of the problems that still often occurs. The area studied in this study is the area most frequently affected by tidal flooding in Tegal City. The areas affected by the tidal flood included Kraton Village, Tegalsari Village, and Muarareja Village. This research, among others, aims to determine the level of community vulnerability to tidal flooding. The data used include: land use data, population data, and primary data through questionnaires to the community. The method used in this research is descriptive quantitative and qualitative descriptive methods. The population in this study were the heads of families from three villages affected by the tidal flood. The vulnerability sample includes the community in three villages affected by the tidal flood which was obtained from the sampling technique in the form of Simple Random Sampling. The results showed that the level of tidal flood vulnerability in the District of West Tegal was included in the medium class in the Kraton Village, and the high class in the Tegalsari Village and Muarareja Village.